To Err is Human, To Forget is Device-related: A Cautionary Note for Endoscopists. (October 2020) - Lesho, Emil; Fede, Jennifer; Vore, Kelly; Bronstein, Melissa
Abstract : Background: In the United States, ∼5 million endoscopies are performed annually. Contaminated endoscopes account for more nosocomial infections than any other medical device, but the vast majority of such events go unreported. We found no reports in the literature or the FDA Manufacturer and User Facility Device Experience (MAUDE) database of the incident described below. Methods: During a colonoscopy, the operator noticed resistance while advancing a clipping wire through the channel. A balloon-tipped catheter sheath was then extruded into the colonic lumen. The sheath and endoscope were withdrawn without incident, and the procedure was completed with a different endoscope. According to equipment logs, the last time that type of balloon-tipped catheter was used occurred 20 days prior, resulting in 20 patients having potentially been exposed to an incompletely disinfected device. Interrogation of the endoscope with various inserts revealed that the presence of a retained sheath would allow passage of all types of guide wires, (snips, snares, etc), including the cleaning brush. The only device whose passage would have been prevented by a retained sheath was a vascular clipping device. A review of procedure notes and interviews of involved physicians revealed that such clippings were performed as recently as 2 days prior to the incident, thus reducing the number of potentially exposed to 2, plus the index. The county and state health departments were notified, a MAUDE report was filed, and patients were notified and offered free testing for bloodborne and enteric pathogens. Discussion: The root causes of the exposure included the absence of a closed-loop feedback for removable components (similar to an operating room sponge count), an inexperienced endoscopy technologist, and, in our opinion, a design flaw of the sheath that allows the sheath to enter the channel. Specifically, unlike other sheath brands, this brand lacks a large, irremovable warning flag that precludes channel entry (Fig. 1). Had we not been able to trace the use of each individual endoscope (n = 45) in the clinic and link each to specific patients, procedures, and reprocessing logs, we would have had no way to determine the extent of exposures. This incident, which we present as a cautionary tail to others, highlights (1) a possible equipment design flaw, (2) the importance of closed-loop feedbacks for removable components, (3) the criticality of detailed procedure notes along with granular cleaning and reprocessing logs traceable to every endoscope, and (4) the challenge of communicating risk of disease transmission to patients. Funding: None Disclosures: None